Comparative Analysis of FY‐3G and GPM Observations on Precipitation Structure and Microphysical Characteristics: A Case of Super Typhoon Krathon - Shengnan Zhou; Yang Gao; Meng Fang; Song Yuan; Yunfei Fu (Earth and Space Science, 2025)
Abstract China's first precipitation measurement satellite, FY‐3G, became operational in April 2024. This study presents the first comparison of Level‐2 Ku‐band precipitation products from FY‐3G and Global Precipitation Measurement (GPM), focusing on the three‐dimensional precipitation structure and microphysical characteristics of Super Typhoon Krathon (2418). Both FY‐3G and GPM observed that convective precipitation dominated the eyewall and stratiform precipitation prevailed in the inner and outer rainbands. However, FY‐3G reported higher overall precipitation intensities than GPM. In the eyewall, both satellites observed that high concentrations (dBNw > 40) of large raindrops (Dm > 2 mm) led to intense precipitation, where droplet concentration was the primary determining factor. FY‐3G exhibited a broader drop size distribution (DSD) for convective precipitation than GPM, while for 10–20 mm/hr stratiform precipitation, both Dm and lgNw had a narrower distribution. The inner rainbands exhibited the most distinct DSD differences, with FY‐3G observing Dm from 0.6 to 2.6 mm, while GPM detected 1.3–2.3 mm with lower lgNw. In the outer rainbands, both satellites observed large raindrops (Dm > 2.1 mm), driven by the super typhoon's radial circulation dynamics. For most stratiform precipitation, FY‐3G showed 1.5–2.0 mm raindrops as the main contributors, while GPM also had a high proportion of 1.0–1.5 mm drops. Both satellites consistently observed 1.5–2.0 mm drops as the main contributors in convective precipitation. Additionally, FY‐3G detected relatively higher number of raindrops smaller than 1.0 mm across various precipitation intensities, which may be primarily attributed to the higher sensitivity of the FY‐3G Precipitation Measurement Radar compared to the GPM Dual‐frequency Precipitation Radar.